Detection of Calcium Crystals in Knee Osteoarthritis Synovial Fluid: A Comparison Between Polarized Light and Scanning Electron Microscopy. Issue 7 (October 2016) - Frallonardo, Paola; Oliviero, Francesca; Peruzzo, Luca; Tauro, Leonardo; Scanu, Anna; Galozzi, Paola; Ramonda, Roberta; Punzi, Leonardo
Abstract : Background: The identification of calcium crystals in synovial fluid (SF) of patients with osteoarthritis (OA) represents an important step in understanding the role of these crystals in synovial inflammation and disease progression. Objectives: This study aimed to investigate the presence of calcium pyrophosphate (CPP) and basic calcium phosphate (BCP) crystals in SF collected from patients with symptomatic knee OA by scanning electron microscopy (SEM) coupled to x-ray energy dispersive spectroscopy, compensated polarized light microscopy (CPLM), and alizarin red staining. Methods: Seventy-four patients with knee OA were included in the study. Synovial fluid samples were collected after arthrocentesis and examined under CPLM for the assessment of CPP crystals. Basic calcium phosphate crystals were evaluated by alizarin red staining. All the samples were examined by SEM. The concordance between the 2 techniques was evaluated by Cohen κ agreement coefficient. Results: Calcium pyrophosphate and BCP crystals were found, respectively, in 23 (31.1%) and 13 (17.5%) of 74 OA SFs by SEM analysis. Calcium pyrophosphate crystals were identified in 23 (31.1%) of 74 samples by CPLM, whereas BCP crystals were suspected in 27 (36.4%) of 74 samples. According to κ coefficient, the concordance between CPLM and SEM was 0.83 for CPP, and that between alizarin red and SEM was 0.68 for BCP. Conclusions: The results of our study showed a high level of concordance between the 2 microscope techniques as regards CPP crystal identification and a lower agreement for BCP crystals. Although this finding highlights the difficulty in identifying BCP crystals by alizarin red staining, the use of SEM remains unsuitable to apply in the clinical setting. Because of the in vitro inflammatory effect of BCP crystals, further work on their analysis in SF could provide important information about the OA process.